Writing for educators : personal essays and practical advice - Bromley, Karen D'Angelo (Emerald Publishing Limited : IAP, 2009)
This book is for new faculty, graduate students, teachers, administrators, and other academics who want to write more clearly and have their work published. The essays focus on writing journal articles, dissertations, grants, edited books, and other writing in educational settings. The authors are educators who share their own first-hand experiences that provide novice writers with important knowledge and support in the quest for success in professional scholarly writing. A variety of authors discuss the writer's craft, including issues of voice, audience, planning, drafting, revision, conventions, style, submitting to journals, editorial review, and editing.